Predatory diversity of two demersal finfish species in the trawling grounds off Veraval - Vivekanandan, E (Indian Journal of Fisheries, 2011)
Nemipterus japonicus is morphologically adapted to predate on small sizedcrustaceans like Acetes and penaeid prawns. Saurida tumbil is adapted to predateon larger and faster prey like finfishes and squids. N. japonicus predates on 35prey groups compared to 22 by S. tumbil. Both the predators are asynchronouscyclic feeders. In a continum between opportunistic and selective feeding, N.japonicus is towards opportunistic feeding and S. tumbil towards selective feeding.There are ontogenetic changes in the predatory pattern of both the species.